The effect of game-based interventions on children and adolescents with autism spectrum disorder: A systematic review and meta-analysis - Gao, Jiaxin; Song, Wei; Huang, Dunbing; Zhang, Anren; Ke, Xiaohua (Frontiers in Pediatrics, 2025)
PurposeThe purpose of this meta-analysis was to conduct a comprehensive evaluation of randomized controlled trials (RCTs) of game-based interventions (GBI) for children and adolescents with autism spectrum disorder (ASD) to identify the clinical efficacy of GBI on core symptoms and other concomitant symptoms of ASD.MethodsPubMed, Web of Science, Embase and the Cochrane Library were systematically searched for articles published until July 2023.ResultsTwenty-four studies with 1,801 patients met the inclusion criteria. The results showed that GBI had a significant positive effect on social skills (g = −0.59, p = 0.004), social behaviors (g = 0.45, p < 0.001), and cognition (g = 0.57, p < 0.001) in children and adolescents with ASD, while the effects of language expression (g = 0.15), anxiety (g = −0.13), and parenting stress (g = −0.51) were small and nonsignificant.ConclusionsThe results of the current meta-analysis showed that GBI was effective in improving social skills, social behaviors and cognition in children and adolescents with ASD in the existing studies and was not significant in improving language skills, anxiety and parental stress, but due to the limited number and low quality of the included studies, the above conclusions need to be validated by conducting more large-sample, high-quality RCTs.Systematic Review Registrationwww.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023390793, identifier: CRD42023390793.